News for Citizens : What is this "Beveridge Report"?
1943-03 1943 1940s 2 pages WHAT IS THIS BEVERIDGE REPORT ?— continued in many European countries. This will help every woman to begin her married life with a trousseau and/or something for the new home according to her circumstances, ability to save, or other qualities. The falling birth-rate has worried economists greatly in the past few years, and young people who long to have several children cannot have them, mainly for economic reasons. So the Beveridge Plan suggests a maternity grant of £4 for every mother of a new baby, and in addition, if she is working, for thirteen weeks the mother draws 36/- a week. This means that she can leave work before the baby is born and also look after it properly for the first few weeks of its life. (The married woman, by the way, may continue voluntarily to pay her contribution to the scheme, but even if she does not she is covered by her husband's payments.) The other main classes of benefit are based on existing schemes of insurance, but have slightly different names and in some cases conditions are attached to them. Unemployment Benefit With a Difference First let us look at unemployment benefit. The first point that must occur to anyone reading of this provision is that, apparently, we are always to have some measure of unemployment, although we must never again have mass unemployment. But this is unemployment benefit with a difference. There is no Means Test, but after a certain lapse of time, if a man or woman cannot be re-employed in their own trade or profession, they must accept training in another trade. During this transition period training benefit will be paid. This provision is an interesting comment on the adaptability of which we have all been proved capable in war-time. Disability benefit will generally be of no fixed duration; that is to say, if a man is ill he will draw disability benefit on a doctor's certificate until he is fit enough to go back to work. Industrial disability will be a weekly payment, too. This distinguishes it from workmen's compensation, where a lump sum is often claimed, a little business bought, the business fails and there is the recipient again a claim on the State. Widows and - What will be the position of a widow under the Beveridge Plan? To-day a widow, of any or no income, can draw a pension of 10/- a week. This admittedly is not much, but, if you are young and fitted to do a job, it means that you are in a position to undercut other women. If, on the other hand, you are old or have a family to provide for, it is less than a basic subsistence allowance. Under the Beveridge Plan, a widow under 60 will get 36/- a week for 13 weeks, and if she is under 60 and has children of school age she will get guardian benefit of 24/- indefinitely, subject to a deduction for any earnings. You will see, therefore, that if a widow is able to do so, she is encouraged to work until the age of 60, when every woman is free to retire on a pension. - Old People Retirement pensions (our present old age pensions) will be granted to men at 65 and to women at 60, but this part of the Plan cannot operate fully until after 20 years. In the meantime there will be a transitional scheme whereby the present level of old age pensions will be raised to the Beveridge level. Finally, a word about children's allowances: an allowance of 8/- a week will be paid for each dependent child after the first, and, if the parent is unable to earn, for the first child also. Who is to Pay? But, it will be said, this Plan sounds very fine, but who is to pay for it, and will the weekly contribution be within everyone's means? The answer to the first question is dependent upon an assumption without which the Plan could not be put into operation, and that is a basic minimum wage for everybody. For this, £3 a week has been tentatively suggested, but not stated in the Report. To answer the second question, we cannot do better than quote Mr. Cole, who says: " That the insured can afford what they are asked to pay much better than they can afford to go without what they are offered in return for it, seems to me self-evident. . . . " The family budgets collected by the Ministry of Labour in 1937-1938 showed the average expenditure of industrial households on social security services to have been more than 6/- a week, exclusive of Trade Union contributions of about 1/4. At this rate, allowing for expenditure on services not covered by the Plan, there looks like being no increase at all for the average household, which stands to get much better all-round service for money." The employer and the State, too, it must be remembered, will pay their share. The Issues Behind the Report This, then, is an attempted outline of the Beveridge Plan, but vastly bigger issues are raised than the mere economic safeguard against want. After the war we all want jobs — and, if possible, not the blind-alley sort — and we want leisure time, rich in the colourful things of body, mind and spirit that our own and other cultures have to offer us. The Beveridge Plan, which cannot work unless there is full employment, offers us all freedom from want. By " full employment " is meant that the whole population of working age can be absorbed in the labour market save for a very small minority for whom provision must therefore be made. (There is at the present time in Britain a state of full employment.) That is a chance that none of us can afford to let slip through ignorance or prejudice, and so our first job is to learn more about the Report, to discuss* its provisions in greater detail and, finally, to try and fit it into our picture of the world we would like to live in. We must remember, too, that to have social security immediately the war is over — the danger period — it is essential that "decisions as to the nature of the Plan, that is to say, as to the organisation of social insurance and allied services, should be taken during the war." Also when we go to a housing exhibition, or to the opening of a new community centre, let us not forget that the full enjoyment of living in a modern, well-planned house, or of acting in a play at our community centre, will to a greater or lesser degree be determined by the adoption or not of the Beveridge Plan. We and the Beveridge Report As we go to press the three-day Parliamentary debate on the Report is just concluded. The Government has accepted the main principles of the Report, but there has been considerable dissension in the House as to when the Plan should come into operation, some M.P.s calling for an immediate application. The Report is now being examined in detail by experts in the different Ministries, and for some months they will be preparing the necessary legislative machinery. There will also have to be consultation with the medical profession and other specialist groups. That the Report might have caused a political crisis is a measure of its vital importance, and therefore it is the duty of every citizen to master the essential outlines. Every sort of help will be given in the Press, both national and specialist, in Clubs, and in discussion groups, but if we are to deserve social security everyone must contribute his intelligent consent to the Plan. The after-war world will not be an easy place for any of us, and apathy will be as dangerous to the future of Britain then as now. Also the Plan itself will be attacked on all sides. It will be attacked by certain vested interests, and it will be more insidiously attacked by those people who are always looking back rather than forward. It is up to us to help bring about in a practical way that Freedom from Want which is one of the Four Freedoms in the Atlantic Charter. WHY " MANNERS " NOW? IT may seem odd to offer people hints on manners just now when it takes all one's energy to cope satisfactorily with living from day to day. If you think a moment, however, it will seem odder still to hope to get on at all without some sort of code of manners, and the war itself has evolved an "etiquette" of its own. Manners are the grease which makes the wheels of daily life go round, so we hope to give you a " Topics " and a Quiz on manners. We hope in this way, too, to remind you that after the war there will be sufficient knives and forks again to puzzle us, and to set out (for present use) the perfect manners in a 'bus queue and all that! "TO START YOU TALKING!" TO start you talking in the Club discussion group " Over to You! " provides many good leading questions. This excellent sixpenny worth (with two illustrations by Arthur Wragg) is put out by the London C.E.T.S., 19, Fitzroy Square, W.1, and is sub-divided into such main sections as "Work and the Lack of it," "Education," "Leisure." The questions are provocative, and up-to-the-minute in their expression, and the discussion hints are vivid. For example: "Have you got a good job?" "No, the pay's bad and there's no chance of promotion. Workmates? Oh, they're all right; we all get on well together. And the work interesting? Yes. when I'm not fed up with it. So when you're not fed up you learn something from it? I suppose so. Take a pride in it, in fact? More or less. You must be a good worker, then? Yet the job itself isn't a good one? What do you get from a 'good job,' simply 'good money'?" * The Y.W.C.A. Education Department is hoping to bring out discussion material on the Report. Let us know what would be of particular help to you. Also, notes for discussion being prepared by the National Council of Social Service Women's Group on Public Welfare will be available to any group wanting them. 243/1/9/3/2